Foxg1: a pleiotropic regulator of telencephalic development - Martynoga, Ben; Martynoga, Benjamin (The University of Edinburgh, 2007)
During embryonic development the telencephalon develops from a simple neuroepithelium to give rise to some of the most complex and multi-functional regions of the adult brain. The molecular mechanisms regulating this dramatic metamorphosis are gradually being elucidated. This thesis focuses on the role of the forkhead box factor Foxgl in the development of the vertebrate telencephalon. Mice mutant for Foxgl exhibit multiple telencephalic defects demonstrative of an important pleiotropic role for Foxgl in telencephalic organogenesis. The results presented here provide a range of novel insights into the function of Foxgl at the molecular level and make an important contribution to the understanding of the mechanisms regulating telencephalic development in general.

Severe hypoplasia of the null mutant telencephalon demonstrates that Foxgl is required for the regulation of telencephalic growth. Experiments described in this thesis provide the most systematic study to date of the mechanisms by which Foxgl regulates this process. Broadly, the results demonstrate that Foxgl is required to maintain progenitor cell fate, at the expense of differentiated cell fate, and to maintain the proliferation rate of progenitors. This is consistent with previously published reports. The earliest requirement for Foxgl in regulating proliferation is shown to be in the rostro-medial telencephalon at embryonic day 10.5 (E10.5). Decreased proliferation in this region is spatially and temporally correlated with a decrease in expression of the putative mitogen Fgf8. This molecular change may also underlie a decrease in the number of apoptotic cells observed in the same region. Following these early, localised, changes in progenitor behaviour, proliferative defects become apparent more globally in the Foxgl'1' mutant and unusually high levels of neuronal differentiation are observed. A few days later, at E15.5, numerous cells with astroglial properties are observed in ectopic positions in the mutant telencephalon. Therefore, in addition to regulating the rate of telencephalic proliferation and differentiation, Foxgl also contributes to the highly regulated process of neural cell type specification.

In addition to telencephalic growth defects, it has been documented that ventral telencephalic cell fates are lost in Foxgl'1 embryos. This dramatic phenotype has received remarkably little attention. This thesis demonstrates that all ventral telencephalic lineages, which give rise to the basal ganglia and neuronal and glial constituents of the cerebral cortex, are completely absent in Foxgl1' embryos. By generating chimeric embryos, consisting of a mixture of Foxgland wt cells, new insights are gained into the mode of action of Foxgl in directing the development of the ventral telencephalon. Most striking of these is the demonstration that Foxgl is required cell-autonomously for the specification of ventral telencephalic fate. Even when provided with appropriate developmental signals produced by wild type cells in the chimeric embryo, Foxgl'1' cells fail to express ventral markers and default to an identity with molecular characteristics of dorsal telencephalic lineages.

The requirement for Foxgl to repress ectopic dorsal genes and to activate ventral genes is consistent with a role in regulating the response to ventralising signals. The hypothesis that Foxgl is required for telencephalic cells to respond appropriately to the ventralising morphogen Shh is advanced. A range of experimental approaches is then taken to test this hypothesis. The hedgehog signalling pathway can be activated in Foxgl' cells, but this activation cannot be translated into ventral identity. Evidence is provided for a role of Foxgl in the regulation of the expression and activity of GIi3, the major antagonist of the hedgehog signalling pathway. Genetic removal of Gli3 on a Foxgl'1' background provides an in vivo test of the significance of this finding. In Foxgl1 ;Gli3' telencephalon, some aspects of ventral telencephalic fate are recovered. This demonstrates that Foxgl is required for ventral fate specification, in part through the antagonism of Gli3 action, consistent with the original hypothesis. However, markers of ventro-medial telencephalic fate are not recovered and ectopic expression of dorsal markers persists in double mutants. From these findings it is argued that Foxgl has hedgehog-independent roles in dorso-ventral patterning of the telencephalon. The nature of these functions is still opaque, but elucidating them will provide exciting challenges for future investigators.